HUBUNGAN ANTARA PENGETAHUAN MENCUCI TANGAN PADA IBU YANG MEMILIKI BALITA DENGAN KEJADIAN DIARE DI PUSKESMAS MARTAPURA - Evi Risa Mariana; Agustine Ramie; Yeni Mulyani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2017)
Clean and Healthy Behaviors (PHBS) are all done on the health behaviors of consciousness so that a family member or family can help themselves in the field of health and can play an active role in the activities - activities play an active role in the health and health-related activities in the community. This study aims to gain knowledge about the relationship between the mother wash his hands who have children with diarrhea in health centers and using design korasional Martapura. The population in this study were all mothers who have children in the Public Health Centre Martapura with a sample size of 35 respondents and using accidental sampling technique. The results showed that most respondents had a good knowledge about the level of knowledge about hand washing that is equal to 71.43%. Also known mothers who have a good level of knowledge that toddler had diarrhea by 40%, whereas mothers who have a good level of knowledge that toddler does not have diarrhea by 60%. Based on the chi-square statistic show P value 0,283 > P α 0,05. It shows us that no correlation between mother’s knowledge with diarhea cases.